2018
DOI: 10.1371/journal.pone.0194263
|View full text |Cite
|
Sign up to set email alerts
|

First aid knowledge, attitude, practice, and associated factors among kindergarten teachers of Lideta sub-city Addis Ababa, Ethiopia

Abstract: BackgroundInjuries are very common and can occur at any point of time in a day. Unintended injuries in kindergarten children are the most common and need immediate life saving care which is known as first aid. This study aimed to investigate knowledge, attitude, practice, and associated factors of first aid among kindergarten teachers of Lideta sub-city Addis Ababa, Ethiopia.MethodA cross-sectional study was conducted among kindergarten teachers. Data was collected using pretested, structured and self-administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
59
8
26

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(115 citation statements)
references
References 16 publications
(31 reference statements)
22
59
8
26
Order By: Relevance
“…In this study, the level of good knowledge about basic life support was found to be 44.4% among non-medical participants. The result was in line with the study conducted in Addis Ababa, 17 Saudi Arabia 9 and Iran 23 which was 40.0%, 40.3%, and 45.8%, respectively. The current study result was lower than the studies conducted in Addis Ababa 50.3%, Saudi Arabia 50%, Egypt 74.3%, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the level of good knowledge about basic life support was found to be 44.4% among non-medical participants. The result was in line with the study conducted in Addis Ababa, 17 Saudi Arabia 9 and Iran 23 which was 40.0%, 40.3%, and 45.8%, respectively. The current study result was lower than the studies conducted in Addis Ababa 50.3%, Saudi Arabia 50%, Egypt 74.3%, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…[14][15][16] Other similar studies, in Saudi Arabia and Addis Ababa also reported that basic life support knowledge was 50.0%, 45.8%, 40.0%, and 50.3%, respectively. 4,9,14,17 Studies in India and Portugal showed that level of education, gender, and income was significantly associated with knowledge score towards basic life support. 18,19 The study in Saudi Arabia revealed that higher income and level of education were significantly associated with higher knowledge score towards BLS.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…34 Therefore, preschool teachers, as important leaders, have an important impact on the health knowledge and behaviors of preschool children. 35,36 The current study found that preschool teachers who participated in the survey had poor cognition of child health knowledge. Without adequate health knowledge, the preschool teachers may not be able to provide effective help and support for the development of healthy behavior for children.…”
Section: Discussionmentioning
confidence: 61%
“…But the scenario has not changed much at least in developing countries. Overall perception and practice among school teachers were found to be poor in India [26], Ethiopia [27] and Egypt [28]. But teachers have great attitude towards learning and giving when required [29][30][31].…”
Section: Results Of Individual Questions Was Compared Between Pretestmentioning
confidence: 99%